Adequate Funding Panacea for Development of Educational Administration and Planning Programme in Tertiary Institutions in Nigeria: Pendanaan yang Memadai Obat mujarab untuk Pengembangan Program Administrasi dan Perencanaan Pendidikan di Perguruan Tinggi di Nigeria - Ogunade, Niyi Jacob; Mohammed, Yahaya Danjuma (Pubmedia Social Sciences and Humanities, 2024)
This paper discussed adequate funding panacea for development of educational administration and planning programme in tertiary institutions in Nigeria. Secondary data were used in the paper. The secondary data were collected from print and online publications. The paper noted that adequate funding of educational administration and planning programme in tertiary institutions will lead to availability of funds for effective administration of educational administration and planning programme, employment of adequate academic staff, provision of modern infrastructure facilities, effective staff training, provision of adequate instructional materials and development of research in educational administration and planning programme. Based on the points identified in the paper, the paper hereby recommended that the governments should increase budgetary allocation for tertiary institutions and preference should be given to educational administration and planning programme which will lead to adequate funds for effective administration, employment of adequate lecturers and provision of infrastructure facilities, instructional resources and development of research programme in educational administration and planning programme.